1986
DOI: 10.1002/sim.4780050515
|View full text |Cite
|
Sign up to set email alerts
|

Selection of variables using ‘independence bayes’ in computer‐aided diagnosis of upper gastrointestinal bleeding

Abstract: SUMMARYIn this paper two problems of computer-aided diagnosis with 'independence Bayes' were investigated: selection of variables and monotonicity in performance as the number of measurements is increased. Using prospective data from patients with upper gastrointestinal bleeding, the stepwise forward selection approach maximizing the apparent diagnostic accuracy was analysed with respect to different kinds of bias in estimation of the true diagnostic accuracy and to the stability of the number and type of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…An alternative generalisation, which remains within the mould of independence Bayes, has been explored by Ohmann et al (1986), Langley & Sage (1994, Singh & Provan (1996), Kontkanen er al. (1999), and others, sometimes called 'selective Bayesian classifiers'.…”
Section: Modifications To the Basic Independence Modelmentioning
confidence: 99%
“…An alternative generalisation, which remains within the mould of independence Bayes, has been explored by Ohmann et al (1986), Langley & Sage (1994, Singh & Provan (1996), Kontkanen er al. (1999), and others, sometimes called 'selective Bayesian classifiers'.…”
Section: Modifications To the Basic Independence Modelmentioning
confidence: 99%
“…Crichton et aL [65,66] reported a small increase in accuracy using five or six selected variables rather than all 41 on a database of acute abdominal pain, although the improvement does not appear to be statistically significant. However, Ohmann et aL [67] warned of the danger of bias in selecting variables; in their study of .. patients with gastrointestinal bleeding, ~ they found that the estimated true diagnostic accuracy generally improved as variables were included. Similarly, in a simulation study of cases of vaginal discharge, Chard and Rubenstein [68] found that optimal diagnostic accuracy was achieved using all variables.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Bayes' theorem can work well when independence is assumed, 6,7,12,15,16 but violations of the independence assumption can degrade diagnostic accuracy. [7][8][9][10] Proposed solutions include rankordering variables according to degree of intercorrelation, 8 selecting variables based on whether they increase diagnostic accuracy, 13,14 or using discriminant function analysis. 10 However, clinicians are urged to use LRs published in medical literature, particularly with regard to the clinical examination, to calculate disease probabilities at the bedside.…”
mentioning
confidence: 99%